2019
DOI: 10.1039/c9fo00375d
|View full text |Cite
|
Sign up to set email alerts
|

Cranberries – potential benefits in patients with chronic kidney disease

Abstract: Patients with chronic kidney disease (CKD) present many complications that potentially could be linked to increased cardiovascular mortality such as inflammation, oxidative stress, cellular senescence and gut dysbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…A range of studies have identified optimized nutrition as one of the best strategies to prevent or reduce the complications in CKD. For example, cranberry consumption known historically as a strategy to treat urinary tract infections, can also be used to decrease inflammation and oxidative stress in CKD (De Almeida Alvarenga et al, 2019). Brazilian açai fruit has also been suggested as a food with anti-inflammatory and anti-oxidant action, and is a rich source of flavonoids (Martins et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A range of studies have identified optimized nutrition as one of the best strategies to prevent or reduce the complications in CKD. For example, cranberry consumption known historically as a strategy to treat urinary tract infections, can also be used to decrease inflammation and oxidative stress in CKD (De Almeida Alvarenga et al, 2019). Brazilian açai fruit has also been suggested as a food with anti-inflammatory and anti-oxidant action, and is a rich source of flavonoids (Martins et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many Vaccinium species are utilized as medicinal plants and ornamental landscape ground cover [5]. The high phenolic compounds having strong antioxidative properties of Vaccinium berries are linked to the prevention of several chronic and degenerative diseases including cancer and cardiovascular disorders [6]. The principle function of those antioxidants is to stop or delay the oxidation of other molecules through inhibiting the initiation or propagation of oxidizing chain reactions by free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…A 2 week CJ supplementation study with 7 mL/kg bodyweight given to men, increased plasma AC and decreased oxidized LDL levels, a heart disease risk factor [29]. It is also of importance that the cranberry anthocyanin metabolites accumulate in the kidney and bladder since cranberry and especially CJ are well known to benefit urinary tract health [30]. The fact that PP metabolites also get into other organs such as the prostate [31], brain and liver are significant as growing evidence that cranberries may have a role in cancer prevention and treatment [32].…”
Section: Discussionmentioning
confidence: 99%